Managing Children with Gaucher Disease: Modern Clinical Recommendations - A. A. Baranov; L. S. Namazova-Baranova; O. S. Gundobina; E. A. Lukina; A. K. Gevorkyan; K. V. Savostyanov; A. A. Pushkov; E. A. Vishnyova; G. B. Movsisyan (Педиатрическая фармакология)
The focus of this article is Gaucher disease — a rare enough hereditary pathology. The authors present the most up-to-date epidemiological data and features of Gaucher disease etiopathogenesis. They offer clinical characteristics for the various types of this disease. The algorithm and crucial steps of differential diagnosis are described in detail. Also, the tactic and algorithms of enzymereplacing therapy (pathogenetic treatement of this hereditary enzymopathy) are carefully presented, together with the modern scheme of managing patients according to the corresponding health care delivery stages.